Examination of language, cognitive, and mathematical skills in childhood endocrine diseases - Çavuşoğlu, Ebrar; Savaş, Merve; Dilek, Emine; Elgörmüş, Yusuf; Kahraman Beğen, Senanur (Frontiers in Psychology, 2024)
Children diagnosed with endocrine disorders may not show typical development and may have difficulties in language, academic and cognitive skills along with social-emotional problems. In this study, children with endocrine disorders were compared with their normally developing peers in terms of language, cognition, mathematical skills and psychosocial characteristics. The aim of this study was to identify possible therapeutic needs in the areas of language, cognition and mathematical skills of children with endocrine disorders who experience school failure. In this way, early evaluation of speech and language disorders and planning of intervention will be possible. 15 children diagnosed with endocrine disorders (8 female, 7 male; mean age: 10, SD: 2) and 15 children with normal development (8 female, 7 male; mean age: 10, SD: 2) participated in the study.The participants were administered the Test of Language Development-Primary: Fourth Edition Turkish Revision (TOLDP-4:T T), Turkish Nonword Repetition Test (TNRT), The Turkish Multilinguals Sentence Repetition Test (LITMUS-TR), Wechsler Intelligence Scale for Children (WISC-R), Problem Solving Test (PST), The Revised Child Anxiety And Depression Scale-Child Version (RCADS-CV), Coopersmith Self-Esteem Inventory (CSEI) and Child Behavior Checklist (CBCL)were applied. The data obtained from the study show that children with endocrine disease show lower performance in language, cognition and mathematical skills compared to their healthy peers, while they do not differ in terms of social emotional status assessed by psychological scales.